2011
DOI: 10.26509/frbc-ec-201213
|View full text |Cite
|
Sign up to set email alerts
|

Labor’s Declining Share of Income and Rising Inequality

Abstract: Labor income has been declining as a share of total income earned in the United States for the past three decades. We look at the past effect of the labor share decline on income inequality, and we study the likely future path of the labor share and its implications for inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 1 publication
3
32
0
6
Order By: Relevance
“…The condition that capital income is more concentrated or unequally distributed than labor income has been confirmed by Piketty (2014) and others. For example, Jacobson and Occhino (2012) found that the concentration index of capital income is always larger than that of labor income in the United States during 1979 to 2007, with the former ranging from 0.62 to 0.84 and the latter ranging from 0.42 to 0.50. Using data from eight industrialized countries in the last three decades of the 20th century, Garc ıa-Peñalos and Orgiazzi (2013) concluded that the distribution of capital income, including interest, rent, dividends annuities, private individual pensions and royalties, is much more unequal than labor earnings.…”
Section: Labor Sharementioning
confidence: 99%
“…The condition that capital income is more concentrated or unequally distributed than labor income has been confirmed by Piketty (2014) and others. For example, Jacobson and Occhino (2012) found that the concentration index of capital income is always larger than that of labor income in the United States during 1979 to 2007, with the former ranging from 0.62 to 0.84 and the latter ranging from 0.42 to 0.50. Using data from eight industrialized countries in the last three decades of the 20th century, Garc ıa-Peñalos and Orgiazzi (2013) concluded that the distribution of capital income, including interest, rent, dividends annuities, private individual pensions and royalties, is much more unequal than labor earnings.…”
Section: Labor Sharementioning
confidence: 99%
“…The IMF (2017), the European Commission (2007) and the Bank for International Settlements (Ellis and Smith, 2007) published reports that documented the decline in the labor share of income and provided several explanations for this trend including the impacts of globalization and technological changes. Jacobson and Occhino (2012), using household data for the United States, indicate that the decline in the labor share made total income less evenly distributed and more concentrated at the top of the distribution, thus increasing income inequalit. According to their results, a 1 percent decrease in the labor share of income increases the Gini coefficient in the United States by 0.15-0.33 percent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, technological innovation and the information revolution yielded rapidly changing job-skill demands, and made many low-skilled jobs replaceable by machines. Taken together, these economic shifts created asymmetric industrial-labor power relations (Jacobson & Occhino, 2012).…”
Section: From Shared Prosperity To Slow and Unequal Wage Growthmentioning
confidence: 99%
“…As a result of all these factors, since 1980, the labor share of national income has trended downward. While there are many ways to measure the labor share, nearly all approaches find that it has declined about 10 percent since 1980, while the capital share of income has increased by over a third (Giovannoni, 2014a;Jacobson & Occhino, 2012;Piketty & Zucman, 2014). 4 This trend is found in virtually all OECD countries (International Labor Organization, 2012;Stockhammer, 2013).…”
Section: From Shared Prosperity To Slow and Unequal Wage Growthmentioning
confidence: 99%